Patient entries in the electronic medical record: an interactive interview used in primary care. - Wald, J. S. (American Medical Informatics Association, 1995)
We describe the development, implementation, and use of a computer-administered patient interview, the Health History Interview, by over 300 new patients in a primary care practice at Boston's Beth Israel Hospital. The interview has been well accepted by patients and rated positively by providers. It electronically captures clinical information directly from patients for use during their initial encounter with a provider. It facilitates aggregate analysis of clinical data for quality improvement efforts, such as aiming preventive medicine interventions at identified problem areas within the clinic. Expectations management has been an important task throughout the project. Increasing use of the interview beyond the 30-40% of new patients who have taken it will require greater communication with patients, greater convenience to patients and providers, and more evidence of the clinical, administrative, and research benefits of the technique. Most important, full implementation will require fundamental changes in physician practice habits and patterns of communication between patients and the health care system, as well as clearly demonstrated cost-benefit improvements through the use of these tools.